Directory of World Cinema. - Berra, John (Intellect, 2010)
With high-profile Academy Award nominations and an increasing number of big-name actors eager to sign on to promising projects, independent films have been at the forefront in recent years like never before. But the roots of such critical and commercial successes as The Hurt Locker and Precious can be traced to the first boom of independent cinema in the 1960s, when a raft of talented filmmakers emerged to capture the attention of a rapidly growing audience of young viewers. A thorough overview of a thriving sector of cultural production, the Directory of World Cinema: American Independent chro.